Winter Wheat Response to Timing of Fungicide Application During the 2020–2021 Growing Season - G. Cruppe; N. Giordano; L. M. Simão; L. Ryan; L. O. Pradella; J. R. Soler; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2022)
Foliar fungicides applied at the flag leaf stage can improve wheat grain yield in Kansas, but there is limited information on the impact of earlier or combined applications of fungicide on wheat grain yield. We conducted a field study in six Kansas locations during the 2020–2021 growing season to evaluate the yield and test weight of the winter wheat variety WB-Grainfield in response to different fungicide application timings. The trial was conducted in a randomized complete block design with four replications to evaluate (1) a non-treated control; Topguard applied at 5 ounces per acre at (2) jointing, (3) heading; and (4) jointing plus heading. The study was conducted in two locations with contrasting soil textures near Ashland Bottoms, in two locations with different previous crops resulting in optimum- and late-sowing dates near Belleville, in one location near Hutchinson, and another near Manhattan. Statistical analysis indicated that for both grain yield and grain test weight, there were significant fungicide timing by location interactions, suggesting that the response to fungicide was location-specific. Grain yield ranged from 28 bushels per acre in the no fungicide treatment in Manhattan to 109.9 bu/a with dual-fungicide in the Belleville field sown at the optimum time. Depending on environment, the increase in yield due to the fungicide application as compared to the untreated control ranged from 0.7 to 8.0 bu/a in the jointing application, from -1.8 to 19.3 bu/a in the heading application, and from -1.4 to 17.7 bu/a in the dual application. Grain test weights ranged from 54.1 pounds per bushel without fungicide in one of the trials near Ashland Bottoms, to 62.8 lb/bu near Hutchinson with the dual fungicide application. Test weight benefits due to fungicide depended on location and ranged from -0.1 to 1.7 lb/bu in the jointing application, from -0.9 to 2.6 lb/bu in the heading application, and from -0.3 to 3.9 lb/bu in the dual application. This research is an initial step in determining the benefits of foliar fungicide timing to winter wheat yield and test weight. The results from this study suggest that benefits are substantial, however, the magnitude depended on the environmental conditions experienced during the growing season.
Keywords: wheat; fungicide; jointing; flag leaf; timing; variety